Gas Chromatography–Mass Spectroscopy-Based Metabolomics Analysis Reveals Potential Biochemical Markers for Diagnosis of Gestational Diabetes Mellitus - Raczkowska, Beata A.; Mojsak, Patrycja; Rojo, David; Telejko, Beata; Paczkowska–Abdulsalam, Magdalena; Hryniewicka, Justyna; Zielinska–Maciulewska, Anna; Szelachowska, Malgorzata; Gorska, Maria; Barbas, Coral; Kretowski, Adam; Ciborowski, Michal (Frontiers in Pharmacology, 2021)
Due to many adverse effects of Gestational diabetes mellitus (GDM) on the mother and foetus, its diagnosis is crucial. The presence of GDM can be confirmed by an abnormal fasting plasma glucose level (aFPG) and/or oral glucose tolerance test (OGTT) performed mostly between 24–28 gestational week. Both, aFPG and abnormal glucose tolerance (aGT) are used to diagnose GDM. In comparison to measurement of FPG, OGTT is time–consuming, usually inconvenient for the patient, and very often needs to be repeated. Therefore, it is necessary to seek tests that will be helpful and convenient to diagnose GDM. For this reason, we investigated the differences in fasting serum metabolites between GDM women with abnGM and normal FPG (aGT-GDM group), with aFPG and normal glucose metabolism (aFPG-GDM group) as well as pregnant women with normal glucose tolerance (NGT) being a control group. Serum metabolites were measured by untargeted approach using gas–chromatography–mass spectrometry (GC–MS). In the discovery phase, fasting serum samples collected from 79 pregnant women (aFPG-GDM, n=24; aGT-GDM, n=26; NGT, n=29) between 24–28 weeks of gestation (gwk) were fingerprinted. A set of metabolites (α–hydroxybutyric acid (α–HB), β–hydroxybutyric acid (β–HB) and several fatty acids) significant in aGT–GDM vs NGT but not significant in aFPG-GDM vs NGT comparison in the discovery phase were selected for validation. These metabolites were quantified by a targeted GC–MS method in a validation cohort consisted of 163 pregnant women (aFPG-GDM, n=51; aGT-GDM, n=44; NGT, n=68). Targeted analyses were also performed on serum collected from 92 healthy womenin the first trimester (8–14 gwk) who were NGT at this time, butin the second trimester (24–28 gwk) were diagnosed with GDM. It was found that α–HB, β–HB and several fatty acids were associated with aGT–GDM. A combination of α–HB, β–HB and myristic acid was found highly specific and sensitive for the diagnosis of GDM manifested by aGT–GDM (AUC=0.828) or to select women at risk of aGT–GDM in the first trimester (AUC=0.791). Our findings provides new potential markers of GDM and may have implications for its early diagnosis.